Clinical studies on juvenile, rapidly progressive and adult periodontitis before and after periodontal therapy (I) - (:unkn) unknown (My University, 1992)
The sample in the present study comprised 36 patients who were referred for treatment of periodontal disease. Twenty-four of them were early onset periodontitis (EOP) patients and 12 were adult periodontitis (AP) patients. Based upon the age, number of involved teeth and the location of diseased sites, the EOP patients were divided into two groups as juvenile periodontitis (JP) and rapidly progressive periodontitis (RPP). All the patients were individually examined both clinically and radiographically. At a baseline examination and 3 months after active therapy, the patients were evaluated for plaque, gingivitis, probing depths and probing attachment levels. Following instruction in proper oral hygiene measures, all of the patients were subjected to periodontal treatment. Treatment comprised scaling and root-planing, occlusal adjustment, tetracycline administration and periodontal surgery with osteoplasty. Results showed that age limits between JP and RPP cannot be drawn with certainty. The mean age for the JP group was 21.83 years and was 30.58 years for the RPP group. The number of involved teeth was found to increase with age. The first molars were the most frequently affected teeth followed by the incisors. Three months after active treatment, the response of periodontal tissues to therapy both in EOP and AP groups was almost identical.
Keywords: Adult; Humans; Middle Aged; Treatment Outcome; Adolescent; Analysis of Variance; Periodontal Index; Periodontitis; Aggressive Periodontitis; Dental Plaque Index